Answer:
-1
Step-by-step explanation:
using PEDMAS(parentheses, exponents, division, multiply, addition, subtraction) to solve the problem
First, multiply (-5)(2) and 2(-3)
(-5)(2) – 2(-3) + 3
=-10-(-6)+3
=-10+6+3
add -10+6
-4+3
Add -4+3
-4+3
=-1
Therefore, (-5)(2) – 2(-3) + 3 is equal to -1
<span>$12,385 APR = 6.9% 5 years= $864.565 monthly payment per $100 is $2.44 $12,385 + $864.565 =$13,222.565/60 =$220.37+ $2.44(2) =$225.25 Monthly</span>
Answer:
Q1) ans-16%
Q2) ans-50%
Q3) ans- 16%
Q4) yes, I think the question 3 and 1 are same
For some unknown reason, Brainly won't post my answer as it assumes the answer has inappropriate words or a link.
So, I added the answer in the attached image.
Kindly check it.
Answer:
The answer is 19305
Step-by-step explanation: